(untitled) (Research, Society and Development, 2022)
This paper is an integrative literature review, under descriptive qualitative design. Its goal is to evaluate the parameters of low intensity laser’s dosimetry in the treatment of lesions caused by pressure and diabetes-related ulcers more largely utilized on scientific evidences. Data was collected from Latin American and Caribbean-based literature available on Ciencias da Saude and Base de Dados de Enfermagem, through Biblioteca Virtual em Saúde; Medical Literature Analysis and Retrieval System Online, through PubMed; Web of Science; Cumulative Index of Nursing and Allied Health and EMBASE, filtered by date from 2016 to 2022. The following controlling and non-controlling key-words were used: low level lighttherapy; LLLT; laser biostimulation, laser therapy, photobiomdulation, wounds and injuries; wound healing; diabetic foot; pressure ulcer. Results: 14 studies were analyzed according to two thematic categories, so an evaluation of the parameters of the Low Intensity Laser used on lesions could be made, according to the following etiologies: diabetic wound and lesion by pressure. Conclusion: All the studies found a positive outlook regarding the use of low intensity laser on the treatment of diabetic-related lesions or the ones caused by pressure. The majority recommended a specific length of red range (558nm-660nm). There were discrepancies regarding the energy applied. Nevertheless, the majority of studies present a window from 3 J/cm2 to 6 J/cm2. The category destined to study diabetes-caused ulcers had the potency of 30mW, on the wide majority of cases. The ones related to lesions caused by pressure showed good results with potencies from 3,6mW to 100mW.